An Innovative Hybrid Modular Converter with H-bridge for High Voltage Direct Current Applications - A. Bhanu Prakash,N. Sai Krishna, N. Vanajatha, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
An H-bridge hybrid modular converter (HBHMC) is proposed for high-voltage direct current (HVDC) applications. It uses a wave-shaping circuit consisting of series-connected full-bridge submodules (FBSMs) at the output of the main H-bridge converter. For a three-phase system, three HBHMCs are connected either in series (series-HBHMC) or in parallel (parallel-HBHMC) across the dc-link. The operating modes of HBHMC, novel modulation strategies for voltage balancing of FBSMs, and control of HBHMC-based HVDC system are presented in this paper. A detailed comparison between HBHMC and other hybrid topologies is performed on the basis of required number of switches and capacitors. The HBHMC has the features of dc fault blocking capability, lower footprint structure, and extra degree of freedom for submodules capacitor voltage balancing. The efficacy of the HBHMC-based HVDC system for three-phase balanced and unbalanced grid conditions and its fault-tolerant capability are validated using PSCAD simulation studies. Furthermore, the feasibility of the proposed converter under normal and dc fault conditions and of the proposed capacitor voltage control scheme is validated experimentally by using a three-phase gridconnected HBHMC laboratory prototype.